Growth and yield performance of wheat (Triticum Aestivum L.) As influenced by combined application of naa and n-fertilizer in two sowing time - Adam, AMM Golam; Jahan, Nargis; Rashid , Parveen (Bangladesh Journal of Botany, 2023)
A field experiment was conducted to investigate the effect of NAA (both as foliar and seed soaking) in combination with different N-levels on growth and yield performance of BARI Gom-25 in two sowing time (November 15 and November 22). The experiment consisted of nine treatments viz. control, F4, SOF0, SOF1, SOF2, SOF3, SOF4, SSF0 and SSF1. Results revealed that seed soaking with 10 ppm NAA in combination with 75% recommended dose nitrogen (RDN) produced tallest plants and maximum number of tillers, leaves, total dry matter per plant with significant variations in majority of case in both the sowing time. In case of November 15 sown wheat, seed soaking with 10 ppm NAA in combination with 75% RDN treatment resulted maximum number of effective tillers per plant (6.67), longest spike (9.75), highest dry weight of spike (16.54 cm), highest number of grains per plant (198.08) and maximum yield per plant (7.75 g). Maximum yield per plant obtained from this best performed treatment was 24.80 and 19.81% higher over 10 ppm NAA in combination with RDN and RDN treatment alone, respectively. Findings showed that seed soaking treatment was more effective than foliar spray treatment and wheat sown on November 15 produced better stimulation than sown on November 22 in majority of case. Out of nine treatments, seed soaking with 10 ppm NAA in combination with 75% RDN resulted higher growth and maximum yield in BARI Gom-25. Bangladesh J. Bot. 52(3): 853-860, 2023 (September)